Nanomaterials for the treatment of heavy metal contaminated water - Baby, Rabia; Hussein, Mohd Zobir; Abdullah, Abdul Halim; Zainal, Zulkarnain (Multidisciplinary Digital Publishing Institute, 2022)
Nanotechnology finds its application almost in every field of science and technology. At the same time, it also helps to find the solution to various environment-related problems, especially water contamination. Nanomaterials have many advantages over conventional materials, such as high surface area, both polar and non-polar chemistries, controlled and size-tunable, easier biodegradation, which made them ideal candidates for water and environmental remediation as well. Herein, applications of non-carbon nanomaterials, such as layered double hydroxides, iron oxide magnetite nanoparticles, nano-polymer composites, metal oxide nanomaterials and nanomembranes/fibers in heavy metal contaminated water and environmental remediation are reviewed. These non-carbon nanomaterials, due to their tunable unique chemistry and small size have greater potentials for water and environmental remediation applications.